Keamanan Surat Masuk Menggunakan Enkripsi AES-128 dengan Verifikasi Kode QR di Inspektorat Provinsi Sumatera Utara - Dodyk Fahlome; Dea Alya (Yayasan Pendidikan Al-Yasiriyah Bersaudara, 2025)
Incoming mail security is essential for maintaining information integrity within the North Sumatra Provincial Inspectorate. This study developed a mail metadata security system using the AES-128 algorithm as the encryption mechanism and QR Code as a verification medium. The encryption input consists of mail metadata representing document identity, including sender, receiver, document number, and message description, which are concatenated, converted into 128-bit blocks, and encrypted through ten rounds of AES-128 transformation. The resulting ciphertext is generated from the encrypted metadata output, transformed into a binary bitstream, and encoded into a QR Code to support secure distribution and authenticity validation. System performance stability was evaluated through Black Box testing of functional components, while encryption accuracy was validated through repeated encryption–decryption trials on multiple metadata samples. The results show that the system can generate valid ciphertext, accurately restore metadata, and provide a QR Code–based verification mechanism for government mail management.